Lokakarya Literasi Digital Sebagai Upaya Pemilahan Berita Hoaks Di Desa Menjing, Kecamatan Jenawi, Kabupaten Karanganyar - Markhamah Markhamah; Atiqa Sabardila; Tri Santoso; Wipit Sapitri; Safrudin Athfalusholeh (IAI Darussalam, 2020)
News hoaks rife produced and spread on social media among young people. The news can trigger disputes and threaten social disintegration. The existence of this phenomenon is due to inaccurate people sorting out news that is shared on social media. Based on the above phenomenon community service aims (1) to socialize news sorting strategies: hoaks, (2) to socialize politeness in spreading news on social media, and (3) to train young people in writing news on social media. These community service activities are carried out in Menjing Village, Jenawi District, Karanganyar Regency. Participants in this community service are members of Karangtaruna Menjing Village, Jenawi District, Karanganyar Regency. The strategy in community service is through workshops and hands-on practice.